Zora Neale Hurston a biography of the spirit - Plant, Deborah G. 1956- (Praeger, 2007)
Explores the life and achievements of Zora Neale Hurston, discussing how she dealt with ill health and funded her projects and exploring her relationships with family members and friends, her influence during the Harlem Renaissance, and more.
Includes bibliographical references and index
Keywords: Hurston, Zora Neale; Hurston, Zora Neale -- 1891-1960; Geschichte 1900-2000; Weibliche Schwarze. Amerika; Authors, American -- 20th century -- Biography; African American women -- Southern States -- Biography; Folklorists -- United States -- Biography; African American authors -- Biography; USA; Biografie